Tecniche internazionalprivatistiche fondate sulla volontà delle parti nel Diritto dell'Unione Europea - Biagioni, Giacomo (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Most measures adopted or currently under examination on the basis of art. 81 TFEU contain rules allowing parties to choose the applicable law. The party autonomy principle is well-known in national legal orders, but the European Union law seems to use it in wider terms than national conflict rules usually do. The paper examines the function of that principle in private international law systems: it rests on the assumption that confl ict rules, even if they refer to party autonomy principle, actually apply and produce their effects only in the course of jurisdictional proceedings. In the light of those preliminary remarks the paper distinguishes several methods for giving effect to party autonomy as a private international law principle. First, it analyses express choice, whose function can be different, depending on the time of the choice. Accordingly, the paper concludes that antecedent choice, successive choice and choice in the course of jurisdictional proceedings have different nature and functions. Then, the same distinction is drawn with respect to implied choice, which is envisaged in quite strict terms under «Rome I» and «Rome II» regulations. Thirdly, the paper evaluates the question of the availability of presumed choice, concluding that in some cases it seems to be envisaged in art. 3 of the «Rome I» regulation. Finally, the paper examines ECJ case-law in matter of company law and surname law (especially judgments in Centros, Überseering, Inspire Art, Cartesio and Grunkin cases). Those judgments are usually regarded as providing for a mechanism of mutual recognition (of companies and of surnames) between Member States. The paper tries to infer from them autonomous confl ict rules based on party autonomy principle about company administration as well as protection of surnames. The concluding remarks outline the relevance of party autonomy principle in the present state of European Union private international law, focusing on the risk of moving the centre of gravity too far away from State sovereignty.
Keywords: European Union; party autonomy; applicable law; conflict rules; choice-of-law agreement; express choice; implied choice; time of the choice; partiesinterests; contractual obligations; noncontractual obligations; successions; divorce; legal separation; depeçage